La gangrène de fournier à Cotonou en république du Bénin.. - AVAKOUDJO, JOSUÉ DEJINNIN GEORGES; HOUNNASSO, PP; Natchagande, G; GANDAHO, KI; TORE SANNI, R; HODONOU, F; AGOUNKPE, MM; PARE, AK (My University, 2013)
La gangrène de fournier à Cotonou en république du Bénin..
Keywords: gangrène; nécrose totale; mortalité élevée